Scabies education and detection at Raudlatul Musthofa junior high school - Eka Puspitasari; Qurrotu A’yuunin Lathifah; H. Hariyanto; Yan Fu'ana (Journal of Community Service and Empowerment, 2023)
Scabies is a skin disease endemic in tropical and subtropical climates that is highly contagious and generally affects groups of people with low socioeconomic conditions, poor personal hygiene and sanitation. This activity aimed to make efforts to prevent, provide education, and assist public health development so that it is expected to improve public health in boarding schools students.  This study aims to make efforts to prevent, provide education, and assist public health development so that it is expected to improve public health in boarding schools. The sample to be analyzed was 19 students from Raudlatul Junior High School. Examination of parasites that cause scabies is done with a skin swab. The results of observations that have been made of Raudlatul Musthofa Junior High School students show that the majority of students have carried out personal hygine well, namely all 19 students (100%) bathing at least twice a day using soap, keeping hands and feet clean, and changing clothes when dirty. A total of 14 students (74%) do not exchange personal items such as towels, do not take turns in clothes, and do not dry clothes in the room. A total of 15 students (79%) cleaned the bed, 18 students (95%) did not lend toiletries such as soap, and 16 students (84%) did not experience symptoms of frequent itching at night, rashes (spots), wounds, or dry and crusty skin. The results of skin swab examinations on 19 students at Raudlatul Musthofa seen under a microscope obtained as many as 13 students (68%) samples contained bacteria and as many as 6 students (32%) samples contained fungi.